(untitled) (Journal of Hama University, 2021)
This research aimed to determine the extent of the EVA’s ability to explain changes in the market value of stocks, by applying on Byblos Bank, and to achieve this, the economic value added Indicator was calculated by making the necessary accounting adjustments to the data extracted from the financial statements of a bank Byblos during the time period from 2010 to 2018. In order to study the extent of the reflection of this indicator in the market value of the bank’s stocks, statistical analysis was used in the SPSS program through the simple regression method. The results of the hypotheses test concluded that the economic value added has no impact or ability to explain the change in the market value fluctuations of the stocks of Byblos Bank listed on the Damascus Stock Exchange.